Hybrid MRI guided radiotherapy in locally advanced cervical cancer: Case report of an innovative personalized therapeutic approach. (January 2020) - Boldrini, L.; Chiloiro, G.; Pesce, A.; Romano, A.; Teodoli, S.; Placidi, L.; Campitelli, M.; Gambacorta, M.A.; Valentini, V.
Highlights: The case report of a patient affected by locally advanced cervical MRgRT is described. MRgRT appears to be feasible for cervical cancer and may improve treatment quality. MRgRT insights are discussed focusing on adaptive response and toxicity monitoring.